Effect of different intensities of transcranial direct current stimulation on postural response to external perturbation in patients with Parkinson’s disease - Beretta, Victor Spiandor [UNESP] (2020)
Background. Habituation of postural response to perturbations is impaired in people with Parkinson’s disease (PD) due to deficits in cortico-basal pathways. Although transcranial direct current stimulation (tDCS) modulate cortico-basal networks, it remains unclear if it can benefit postural control in PD. Objective. To analyze the effect of different intensities of anodal tDCS on postural responses and prefrontal cortex (PFC) activity during the habituation to the external perturbation in patients with PD (n = 24). Methods. Anodal tDCS was applied over the primary motor cortex (M1) with 1 mA, 2 mA, and sham stimulation in 3 different sessions (~2 weeks apart) during 20 minutes immediately before the postural assessment. External perturbation (7 trials) was applied by a support base posterior translation (20 cm/s and 5 cm). Primary outcome measures included lower limb electromyography and center of pressure parameters. Measures of PFC activity are reported as exploratory outcomes. Analyses of variance (Stimulation Condition × Trial) were performed. Results. Habituation of perturbation was evidenced independent of the stimulation conditions. Both active stimulation intensities had shorter recovery time and a trend for lower cortical activity in the stimulated hemisphere when compared to sham condition. Shorter onset latency of the medial gastrocnemius as well as lower cortical activity in the nonstimulated hemisphere were only observed after 2 mA concerning the sham condition. Conclusions. tDCS over M1 improved the postural response to external perturbation in PD, with better response observed for 2 mA compared with 1 mA. However, tDCS seems to be inefficient in modifying the habituation of perturbation.